Seeing the Rock: Expanding One’s Vision in Community with Preschool Knowers - Furman, Cara (Philosophical Inquiry in Education, 2021)
This paper takes a philosophically informed approach to what it means to make sense of the world. Specifically, it asks how understanding might be enhanced when we listen to young children who are labelled with disabilities. To address this question, I describe a lesson I taught as a guest teacher in which my understanding of both a rock and an activity, descriptive inquiry, were challenged and expanded through the participation of a child identified with a significant language-based disability. To explore this event and its implications for what it means to teach and know, I juxtapose Jacques Derrida, Miranda Fricker, and Jacques Rancière with each other and with my descriptions of the event.